Стоматологический статус и биохимические показатели ротовой жидкости при сахарном диабете ii типа = Dental status and biochemical indicators in oral liquid type ii diabetes - Alexandra Skiba; Oksana Denga; Olga Makarenko (Kazimierz Wielki University, 2015)
Skiba A. V., Denga O. V., Makarenko O. A. Стоматологический статус и биохимические показатели ротовой жидкости при сахарном диабете II типа = Dental status and biochemical indicators in oral liquid type II diabetes. Journal of Education, Health and Sport. 2015;5(12):493-502. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35915 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A493-502 http://pbn.nauka.gov.pl/works/685612 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 15.12.2015. Accepted: 23.12.2015.   УДК: 616.31-08-039.71:616.379-008.64 UDC: 616.31-08-039.71:616.379-008.64   СТОМАТОЛОГИЧЕСКИЙ СТАТУС И БИОХИМИЧЕСКИЕ ПОКАЗАТЕЛИ РОТОВОЙ ЖИДКОСТИ ПРИ САХАРНОМ ДИАБЕТЕ II ТИПА   DENTAL STATUS AND BIOCHEMICAL INDICATORS IN ORAL LIQUID TYPE II DIABETES   А. В. Скиба, О. В. Деньга, О. А. Макаренко A. V. Skiba, O. V. Denga, O. A. Makarenko   ГУ «Институт стоматологии Национальной академии медицинских наук Украины» SE "Institute of Stomatology of NAMS of Ukraine"   Реферат Сахарный диабет II типа составляет 85-90 % от всех заболеваний, связанных с повышенным содержанием сахара в крови. Оксидный стресс и нарушения метаболизма являются одной  из причин поражения тканей полости рта  и диктуют необходимость разработки эффективных методов профилактики заболеваний полости рта. Целью работы была оценка распространенности и степени воспаления тканей пародонта, биохимических показателей ротовой жидкости пациентов с сахарным диабетом II типа при профилактических мероприятиях. Материалы и методы. В исследованиях участвовали пациенты 30-60 лет с сахарным диабетом II типа (53 человека). При этом оценивались стоматологический статус, а также в ротовой жидкости активность эластазы, каталазы, лизоцима, уреазы, степень дисбиоза, содержание малонового диальдегида. Пациенты основной группы получали 2 раза в году  разработанный и согласованный с терапевтом лечебно-профилактический комплекс. Результаты. Выводы. Разработанный комплекс профилактики и лечения стоматологических заболеваний для пациентов с сахарным диабетом II типа обладает длительным стойким клиническим эффектом, снижает распространённость воспаления практически в 2 раза при I-III степени пародонтита,  снижает в полости рта степень дисбиоза в 7,3 раза через 12 месяцев, увеличивает в 2 раза активность лизоцима в ротовой жидкости (неспецифическая резистентность) и улучшает антиоксидантную защиту (в 3,9 раза уменьшает содержание малонового диальдегида).   Ключевые слова: сахарный диабет II типа, стоматологический статус, ротовая жидкость, биохимические параметры, профилактический комплекс.           A. V. Skiba, O. V. Denga, O. A. Makarenko,  SE "Institute of Stomatology of NAMS of Ukraine" DENTAL STATUS AND BIOCHEMICAL INDICATORS IN ORAL LIQUID TYPE II DIABETES Abstract Type II diabetes is 85-90% of all diseases associated with high blood sugar. The oxide stress and metabolic disorders are one of the reasons for the defeat of the oral tissues and necessitate the development of effective methods of prevention of oral diseases. The aim of the work was to evaluate the prevalence and degree of inflammation of periodontal tissues, biochemical indices of oral liquid patients with type II diabetes mellitus in the prevention activities. Materials and methods. The study included patients 30-60 years with diabetes mellitus type II (53 persons). When this estimated dental status, as well as oral liquid elastase activity, catalase, lysozyme, urease, the degree of dysbiosis, malonic dialdehyde. Patients of the main group received 2 times per year developed and agreed with the general practitioner and treatment and prophylactic complex. Results. Conclusions. The developed complex of therapeutic measures for patients with type II diabetes has a long persistent clinical effect, reduces the prevalence of inflammation in almost 2 times with I-III degree of periodontitis in the oral cavity, reduces the degree of dysbiosis 7.3 times in 12 months, 2-fold increase in the activity of lysozyme in saliva (nonspecific resistance) and improves antioxidant defense 3.9 times reduces the content of malondialdehyde).   Keywords: type II diabetes, dental status, oral fluid, biochemical parameters, preventive complex.